The Politics of Evidence and Results in International Development: Pla ying the Game to Change the Rules? - Eyben, Rosalind; Guijt, Irene; Roche, Chris; Shutt, Cathy (Practical Action Publishing, 2015)
Understanding and demonstrating the effectiveness of efforts to improv e the lives of those living in poverty is an essential part of interna tional development practice. But who decides what counts as good or cr edible evidence? Can the drive to measure results do justice to and pr omote transformational change change that challenges the power relatio ns that produce and reproduce inequality, injustice and the non-fulfil lment of human rights? The Politics of Evidence in International Devel opment provides a critical examination of the results agenda, with pra ctical strategies for rendering it more helpful in supporting transfor mative development. The book deconstructs the origins and concepts of the results and evidence agendas employed in international development . It describes with concrete examples the current effects and conseque nces of the agenda, and goes on to outline a range of strategies used by individuals and organizations to resist, adapt or comply with the u seful and problematic demands for results-oriented measurement and evi dence of value for money."